Pembinaan Keagamaan dalam Meningkatkan Religiositas Narapidana dan Implikasinya dalam Bimbingan dan Konseling - Said Ikhwani; Muhammad Nasir; Marimbun Marimbun (Prodi Bimbingan dan Konseling Islam, 2021)
The purpose of this research is religious development in increasing religiosity, how to respond to descriptions and how the results of religious development activities are. Qualitative research method with a descriptive approach. The research subjects were prisoners, Ustadz, and correctional officers. Data collection techniques are observation and interviews. Data analysis through data reduction, data presentation, and drawing conclusions. The results of the study indicate that urgent religious development is held in correctional institutions in collaboration with several institutions such as the Islamic Shari'ah Service, the Syari'ah Court, the Indonesian Da'i Association, the Ulema Consultative Council, and the Darul Mukhlisin Islamic Boarding School in Aceh Tamiang. The results of this collaboration confirmed the Al-Hikmah Islamic Boarding School in the Correctional Institution. The existence of the Al-Hikmah Islamic Boarding School helps religious development in the form of congregational prayers, dhikr, prayer, reading the Koran, cults, and studying books, and conducting religious studies filled by several ustadz from outside the prison. The response to religious development activities was initially very refusal, but gradually the people realized the benefits of these activities. The religious guidance carried out has an effect on increasing the religiosity of the inmates so that religious behavior can be seen in various religious activities.